Penerapan Strategi Pembelajaran Inklusif di Madrasah atau di Sekolah - Nila Komala Bintang; Harisma Juliani; Gusmaneli Gusmaneli (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
Implementing inclusive learning strategies in madrasas or schools is an approach that aims to emphasize the importance of inclusion and acceptance for all students without exception. In an educational context, inclusive strategies can include a variety of learning methods and techniques that enable every student, including those with special needs, to learn effectively and feel welcome in the educational environment. Inclusive learning strategies in madrasas or schools can involve the use of differentiation approaches, collaboration between teachers and other educational staff, the use of technology that supports needs-based learning, as well as approaches that focus on the diversity and uniqueness of each student. Through implementing this inclusive strategy, it is hoped that every student can receive quality education and meet their individual learning needs. Thus, implementing inclusive learning strategies in madrasas or schools is not only important to improve the quality of education, but also to realize the vision of education that is inclusive, fair and equal for all students. Therefore, the role of teachers, teaching staff, parents and all related parties is very important in supporting and implementing inclusive learning strategies effectively and sustainably. This research uses a literature review method by searching for related sources.